The Polish-language version of the French grammar book by François de Wailly (1792) in light of Onufry Kopczyński’s grammatical terminology - Jakubczyk, Marcin (Papers in Linguistics, 2024)
Applying the research methodology used in the history of linguistics, the study presents a synthesis of Polish grammatical terminology included in the grammar book of French written by François de Wailly, translated into Polish by Kajetan Kamieński. The work covers the subject matter including phonetics, spelling, morphology, syntax, and punctuation. The article discusses approximately a hundred Polish grammatical terms, and on this basis a conclusion is drawn that the translation by Kamieński proves to be a modern grammar, containing the latest Polish grammatical nomenclature of the current time, codified by Onufry Kopczyński in Gramatyka dla szkół narodowych [‘Grammar book of Polish for national schools’] (1778–1785). This shows that Kamieński took most of the terms from Kopczyński’s work. The study is the first analysis of the Polish-language version of the grammar book by de Wailly in literature on lingustics.